2017
DOI: 10.3892/ijo.2017.3945
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 inhibits proliferation and migration of breast cancer cells by directly or indirectly regulating TGF-β1 expression

Abstract: Studies have demonstrated low expression of miR-145 associated with cell proliferation and migration in a wide variety of tumors. Here, we studied the expression of miR-145 in relation to the occurrence and development of breast cancer. Total RNA from breast cancer tissue and corresponding adjacent normal tissue was extracted and used to detect miR-145 expression by quantitative real-time polymerase chain reaction (qRT-PCR). We also transfected breast cancer cells with hsa-miR-145 mimics, hsa-miR-145 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 35 publications
6
61
0
Order By: Relevance
“…Moreover, cancer cells silenced with siRNA against COL5A1 showed reduced cell invasion, demonstrating the association of higher COL5A1 expression with metastasis in many tumors including our TSCC patients . Previous studies showed that low expression of miR‐145 is associated with cell proliferation and migration in a wide variety of tumors and co‐expression of higher COL5A1 and low miR‐145 was detected in primary meningioma tissues, representing an indirect effect on COL5A1 transcriptional regulation . Regulation of COL5A1 by miR‐145 will need to be further verified in TSCC.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, cancer cells silenced with siRNA against COL5A1 showed reduced cell invasion, demonstrating the association of higher COL5A1 expression with metastasis in many tumors including our TSCC patients . Previous studies showed that low expression of miR‐145 is associated with cell proliferation and migration in a wide variety of tumors and co‐expression of higher COL5A1 and low miR‐145 was detected in primary meningioma tissues, representing an indirect effect on COL5A1 transcriptional regulation . Regulation of COL5A1 by miR‐145 will need to be further verified in TSCC.…”
Section: Discussionmentioning
confidence: 74%
“…miR‐145 is a newly discovered miRNA, which is significantly less expressed in breast cancer (Ding et al, ), cervical cancer (Sathyanarayanan et al, ), glioma (Xu et al, ), colon cancer (Li et al, ), esophageal cancer (Zhang et al, ), and non‐small‐cell lung cancer (Yin et al, ). The genes regulated by miRNA‐145 are different in different tumors, and the molecular mechanisms of their anti‐cancer effects are also different.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al verified that miR-145 acts as a tumor suppressor and that its downregulation in tumor tissues may contribute to the progression of BRCA through a mechanism involving ROCK1 [28]. Ding et al suggested that miR-145 may inhibit TGF-beta1 protein expression, which may in turn induce the initiation and progression of BRCA [29]. In this research, miR-145 was found to be expressed at notably low levels in BRCA tissues and cells, and overexpression of miR-145 remarkably promoted cell apoptosis in BRCA by regulating CCNE2.…”
Section: Discussionmentioning
confidence: 99%